Tuning Hierarchical ZSM-5 Zeolite for Both Gas- And Liquid-Phase Biorefining - Zhao, Shufang; Wang, Wei David; Wang, Lizhuo; Schwieger, Wilhelm; Wang, Wei; Huang, Jun (ACS Catalysis, 2020)
A hierarchical ZSM-5 zeolite with an adjustable mesoporous size is required for many chemical processes including the biorefining of big biomass compounds. In this research, a simple and high-efficiency hard template method has been successfully developed by adopting carbon nanoparticles obtained from carbonation of polyethylene oxide and urea. The abundant -C-O-C- groups on the surface of carbon nanoparticles provide the high hydrophilicity (from -C-O-C- to -C-O-H) in the alkaline synthetic gel solution, which promotes the synthesis of hierarchical ZSM-5 zeolite and the aluminum condensation in the silica framework to improve the Brønsted acidity. The as-synthesized hierarchical zeolites exhibited two sets of channel systems: micropores (∼0.55 nm) are from the MFI framework network, and mesopores (∼12.5 and ∼34.5 nm) result from carbon nanoparticles of 10-40 nm in size, respectively. The hierarchical ZSM-5 with minimized extraframework aluminum species showed catalytic performance with high ethanol conversion (100%) and high stability (lifetime above 30 h) in the ethanol to olefins conversion. Importantly, the diffusion efficiency in ZSM-5 with mesoporous size was remarkably improved, compared to the catalyst with mesoporous size ∼12.5 nm. As the benzylation of mesitylene with benzyl alcohol, the ZSM-5 (∼34.5 nm) sample showed the highest conversion in benzyl alcohol (82.0%) and selectivity in 2-benzyl-1,3,5-trimethylbenzene (74.3%).
CRIS-Team Scopus Importer:2020-02-07
Keywords: benzylation; Brønsted acidity; carbon particles; ethanol dehydration; hierarchical ZSM-5 zeolites